Model of good corporate governance: a study of commercial banks in ASEAN5 - Ramly, Zulkufly; Sok, Gee Chan; Sapiei, Noor Sharoja; Mustapha, Zulkhairi (2014)
Due to the increasing roles of bank governance after the Global Financial Crisis, Basel III gives great emphasis on the role of the board of directors in ensuring a long‐term survivability of the banking industry. This study aims to examine the relationship between board structures, board monitoring and board diversity towards the efficiency of selected commercial banks in ASEAN5 from 1998 to 2012. This study focuses on the directors’ characteristics and diversity, which are essential elements of a sound corporate governance framework. Ultimately, this study seeks to develop a model of corporate governance that can contribute to a superior banks’ performance in this region. The Data Envelopment Analysis (DEA) model will be employed to estimate the profit efficiency scores of the selected commercial banks. The profit efficiency score is a better measure of bank’s performance than financial ratios because it takes into consideration the utilization of inputs in achieving a given level of profit. Besides, this study will employ panel data estimation based on Tobit Regression and Structural Equation Modeling to investigate the relationship between board structures, monitoring and diversity towards the efficiency of commercial banks in ASEAN5.